2010
DOI: 10.1021/jp1068413
|View full text |Cite
|
Sign up to set email alerts
|

Density and Surface Tension of Ionic Liquids

Abstract: We measured the density and surface tension of 9 bis[(trifluoromethyl)sulfonyl]imide ([Tf(2)N](-))-based and 12 1-methyl-3-octylimidazolium ([C(8)C(1)Im](+))-based ionic liquids (ILs) with the vibrating tube and the pendant drop method, respectively. This comprehensive set of ILs was chosen to probe the influence of the cations and anions on density and surface tension. When the alkyl chain length in the [C(n)C(1)Im][Tf(2)N] series (n = 1, 2, 4, 6, 8, 10, 12) is increased, a decrease in density is observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
238
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(280 citation statements)
references
References 92 publications
34
238
7
1
Order By: Relevance
“…. These values agree well with the calculations of Kolbeck et al [57] We can study the efect of the volume of the ion in the global V m . The ionic volume is a measure of the size of an ion, equally valid for symmetrical and nonsymmetrical ions.…”
Section: Estimation By Group Contribution Methods (Gcmssupporting
confidence: 91%
“…. These values agree well with the calculations of Kolbeck et al [57] We can study the efect of the volume of the ion in the global V m . The ionic volume is a measure of the size of an ion, equally valid for symmetrical and nonsymmetrical ions.…”
Section: Estimation By Group Contribution Methods (Gcmssupporting
confidence: 91%
“…The influence of the anion on the densities has been explored previously by Kolbeck et al 90 and later by Neves et al 58 In both studies, it was found that the density increases with increasing molar mass of the fluorinated anions, while a reverse trend is observed for the cyano-based anions. One of the explanations for these tendencies was the fact that the introduction of a fluorine atom has a strong influence on the molar weight of a molecule.…”
Section: Densitymentioning
confidence: 88%
“…At this interface, the composition of, and molecular arrangement at, the surface will be different to the bulk due to the unbalanced forces, which are present as a result of the non-isotropic environment. An understanding of the IL interfaces at a molecular level is also crucial in order to explain fundamental macroscopic surface properties such as surface tension [ 79,80 ] and electron transfer processes in electrochemistry. [ 3 , 81 ] The discussion on IL surface structure often involves two different but interrelated aspects: surface composition and molecular orientation at the surface.…”
Section: The Ionic Liquid-vacuum Interfacementioning
confidence: 99%